Self-Handicapping and Its Value in Sports - Yetkin Utku Kamuk (Türk Spor ve Egzersiz Dergisi)
Self-handicapping can be defined as an effort to voluntarily create excuses that an individual can use in case of potential failure. Self-handicapping behavior, which can be manifested either behaviorally or verbally, helps protecting the self-esteem of the individual in short-term, but causes psychological/social problems if used frequently. Studies on self-handicapping in the literature are generally concentrated in the academic field. The method used in this study was reviewing th original articles related to the topc self-handicapping and sports. There are frequent studies on self-handicapping levels of academic staff, students and teachers. This study was carried out to examine the studies on self-handicapping in the field of sports. The number of studies in the field of sports is limited. In studies investigating which variables were affected by self-handicapping, it was seen that sociodemographic variables did not affect the level of self-handicapping, but there was a controversion in the gender variable because there were conflicting findings regarding the effect of gender on self-handicapping levels. There were also studies reporting that self-handicapping was associated with self-esteem and examined it. It was reported that self-esteem had a negative correlation with self-handicapping, and individuals with high self-esteem tended to have low self-handicapping behavior. In the sports performances, the value attributed by the individual to this performance (competition or performance test) affected the self-handicapping tendency of the athlete. As the importance of performance increased, the tendency of athletes to self-hadicapping also increased. In team sports, athletes' tendency to claimed self-handicapping behavior may lead to negative consequences such as exclusion of athletes from the team. It was concluded that the studies on self-handicapping in sports focused on athletes and referees, but there were no studies investigating the self-handicapping tendencies of coaches. Studies on disabled athletes were limited. It was considered that increasing the number of studies conducted in the field of sports, especially on disabled athletes and trainers, would fill the gap in this field.